Niacin Reverses Migratory Macrophage Foam Cell Arrest Mediated by oxLDL In Vitro - Huang, Hua; Koelle, Pirkko; Fendler, Markus; Schroettle, Angelika; Czihal, Michael; Hoffmann, Ulrich; Kuhlencordt, Peter Jan (PLOS ONE, 2014)
Introduction Niacin reduces vascular oxidative stress and down regulates inducible nitric oxide synthase, an enzyme mediating proatherosclerotic effects in part by increasing oxidative stress. Here, we evaluate whether Niacin reverses the redox sensitive migratory arrest of macrophages in response to oxidised(ox) LDL uptake. Material and Methods Migration of RAW264.7 cells, a murine macrophage cell line and bone marrow derived macrophages from wildtype and iNOS knockout mice was quantified using a modified Boyden chamber. Unstimulated cells or cells preincubated with oxLDL or non-oxidised (n)LDL were treated with Nicotinic acid or Nicotinamide. Nitric oxide, peroxynitrite and ROS production were assessed using electron paramagnetic resonance (ESR). Additionally, flow cytometry analysis of apoptosis, fokal adhesion kinase (FAK), phalloidin, CD36, F4/80 macrophage marker and iNOS gene expression (PCR) were assessed. Results Migration of Nicotinic acid, Nicotinamide treated cells or unstimulated cells did not differ (P>0.05). oxLDL treatment significantly reduced migration vs. unstimulated cells (p<0.05). In contrast, migratory arrest in response to oxLDL treatment was reversed by co-incubation with Nicotinic acid and Nicotinamide. The oxLDL-induced peroxynitrite formation in RAW264.7 cells was abolished by Niacin and glutathion (GSH) oxidation was significantly reduced. However, nitric oxide (NO)- and reactive oxygen species (ROS) production induced by oxLDL were not affected by Niacin treatment of RAW264.7 cells. In addition, Nicotinic acid and Nicotinamide reduced actin polymerization, a marker for migratory arrest. Discussion Our data shows that oxLDL induced inhibition of macrophage migration in vitro can be reversed by Niacin. Furthermore, Niacin reduces peroxynitite formation and improves antioxidant GSH.